2015
DOI: 10.1016/j.ijcha.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Could early septal involvement in the remodeling process be related to the advance hypertensive heart disease?

Abstract: BackgroundQuantitative imaging analyses showed an earlier septal wall involvement in hypertension. We planned to determine the effect of hypertension on regional myocardial performance index (MPI) in a hypertensive patient population.MethodsWe evaluated 119 hypertensive patients who were divided into gr. I: 57 patients without left ventricular hypertrophy (LVH), (53.1 ± 10 years), and gr. II: 62 patients with LVH (55.1 ± 9 years) using conventional and tissue doppler imaging. They were compared with gr. III, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…The lateral LV segment was affected to a lesser extent whereas the inferior and posterior walls were unaltered. Previous studies have shown that the septal wall has a greater sensitivity to fibrosis [48] and increased septal myocardial stress has been associated with early structural remodelling in patients with HFpEF [49]. To the best of our knowledge, the present study is the first to demonstrate associations between inflammatory markers with early myocardial deformation in an animal model of RA.…”
Section: Plos Onesupporting
confidence: 51%
“…The lateral LV segment was affected to a lesser extent whereas the inferior and posterior walls were unaltered. Previous studies have shown that the septal wall has a greater sensitivity to fibrosis [48] and increased septal myocardial stress has been associated with early structural remodelling in patients with HFpEF [49]. To the best of our knowledge, the present study is the first to demonstrate associations between inflammatory markers with early myocardial deformation in an animal model of RA.…”
Section: Plos Onesupporting
confidence: 51%
“…Functional impairment of the septal base in the early stage may progress more severely in the disease process. In fact, we recently have demonstrated blunted septal mechanical performance compared with the lateral wall in advanced hypertensive disease (39). A clinical study using cardiac magnetic resonance imaging (27) showed that the initial period of LV remodeling under intensive exercise training is associated with asymmetric hypertrophy of the septal base, the closest part of myocardium to increased aterload that is possibly affected by hemodynamic load (2,3,5,29).…”
Section: Discussionmentioning
confidence: 99%
“…Preserved cardiac energy metabolism was another consistent finding in the pressure-overload model before the development of heart failure in Dahl salt-sensitive rats [ 42 ]. Moreover, even we use the terminology of global LV remodeling for advance cases with hypertensive heart disease; we detected predominant septal geometry and more severe septal dysfunction than free wall in this group and speculated that the early involvement of the septum by BSH could possibly be a reason for more severe regional involvement in the LV septum with progression of the disease process [ 43 ].…”
Section: Effective Medical Approach In Hypertensive Diseasementioning
confidence: 99%